Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1046/j.1525-1497.1999.08108.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and risks of third-generation oral contraceptives

Abstract: OBJECTIVE:To evaluate the risks and benefits of thirdgeneration oral contraceptives. DATA SOURCES: When used consistently, oral contraceptives are a highly effective means of birth control. However, some women discontinue their use because of bothersome side effects such as acne, hirsutism, and weight gain. Oral contraceptives adversely affect thrombolysis, carbohydrate metabolism, and lipid profiles, and this may be why they have been associated with an increased risk of myocardial infarction and stroke in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 67 publications
(97 reference statements)
1
17
0
Order By: Relevance
“…Other studies have shown an increased risk of MI for older COC users and smokers. 66,67,[69][70][71][72] The mortality attributable to COC use among smokers younger than age 35 is 1 per 100 000. The mortality rate significantly increases to 1 per 7000 for smokers older than 35 years of age.…”
Section: Risk Factors For MI and Stroke Among Hc Usersmentioning
confidence: 99%
“…Other studies have shown an increased risk of MI for older COC users and smokers. 66,67,[69][70][71][72] The mortality attributable to COC use among smokers younger than age 35 is 1 per 100 000. The mortality rate significantly increases to 1 per 7000 for smokers older than 35 years of age.…”
Section: Risk Factors For MI and Stroke Among Hc Usersmentioning
confidence: 99%
“…The main risk was initially thought to be related to the oestrogen component and therefore various progestins were developed so that the oestrogen doses in COCs could be reduced (23). Apart from a wish to minimise these major side effects of COCs, there was also an attempt to decrease the level of androgen activity of the progestins, which led to the development of a third generation of COCs (24,25). The aim was to reduce the minor side effects of progestins, such as acne, hirsutism, and weight gain.…”
Section: Hormonal Contraceptionmentioning
confidence: 99%
“…These new progestins, beside having a strong progestational action, also exert anti-estrogenic, antigonadotropic, and antimineralocorticoid effects (Africander et al 2011). Among these, there are the third-generation progestins (desogestrel or gestodene), derived from LNG group, developed to decrease androgenic activity (LeBlanc & Laws 1999), and the fourth-generation progestins. In this latter group, nomegestrol acetate exhibits partial anti-androgenic activity (Lello 2010, Van Diepen et al 2011) DNG, DRSP, and trimegestone have a significant anti-androgenic activity, whereas nestorone has no activity via the AR (Fotherby 1990, Philibert et al 1999, Schindler et al 2003.…”
Section: Figurementioning
confidence: 99%